2005
DOI: 10.1007/s00186-005-0034-4
|View full text |Cite
|
Sign up to set email alerts
|

Zero-sum constrained stochastic games with independent state processes

Abstract: We consider a zero-sum stochastic game with side constraints for both players with a special structure. There are two independent controlled Markov chains, one for each player. The transition probabilities of the chain associated with a player as well as the related side constraints depend only on the actions of the corresponding player; the side constraints also depend on the player's controlled chain. The global cost that player 1 wishes to minimize and that player 2 wishes to maximize, depend however on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…This kind of transition structure is natural, and has already been considered in applications. For applications in wireless networks, Altman et al (2005) (see also Altman et al 2007a,b) examined two-player product-games, although in a somewhat different fashion. They assumed that the sum of the payoffs is always equal to zero (zero-sum games), and dropped the assumption of full monitoring by letting each player observe only his own coordinate of the current state and the action chosen by himself.…”
Section: Strategies a Mixed Action X Imentioning
confidence: 99%
“…This kind of transition structure is natural, and has already been considered in applications. For applications in wireless networks, Altman et al (2005) (see also Altman et al 2007a,b) examined two-player product-games, although in a somewhat different fashion. They assumed that the sum of the payoffs is always equal to zero (zero-sum games), and dropped the assumption of full monitoring by letting each player observe only his own coordinate of the current state and the action chosen by himself.…”
Section: Strategies a Mixed Action X Imentioning
confidence: 99%
“…These examples showed that Jammer pays less attention to the sub-channel with bad quality and Transmitter takes an opportunity to send some part of information over bad quality sub-channels. (2) and (3) we have that Proof of Lemma 1. (i1) For fixed ω > 0 and 0 ≤ ν 1 < ν 2 we have I 10 (ω, ν 1 ) ⊆ I 10 (ω, ν 2 ) and I 11 (ω, ν 1 ) ⊇ I 11 (ω, ν 2 ).…”
Section: Discussionmentioning
confidence: 93%
“…In [2] the authors have studied the application of dynamic stochastic zero sum game to the jamming problem in wireless networks. In the model of [2] the transmission power can be chosen from a discrete set.…”
Section: Introduction and Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations